Implementation of Mathematics Instructional Multimedia for Students’ Self-Regulated Learning - Akmalia, Nela; Rusijono, Rusijono; Arianto, Fajar (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
To face global competition, proper preparation, and superior and qualified human resources are needed. The characteristics of a quality individual are being able to be independent, willing, and capable. Efforts that can be made in forming independent and capable individuals are by training and forming students to develop their self-regulated learning. In learning mathematics, fostering the affective domain requires self-regulated learning which will then form a strong tendency which is called a mathematical disposition. To increase student self-regulated learning, teachers can modify learning, one of which is through the use of learning multimedia. This research is a quantitative study using quasi-experimental methods and the research design used is a static group comparison. The subjects of this study were class VII students at MTs Bilingual Muslimat NU Sidoarjo. Students were divided into two groups: the experimental group consisted of 31 people and the control group consisted of 31 people. Based on the results of data analysis and discussion of research results, it can be concluded that the application of interactive multimedia mathematics affects students’ self-regulated learning. This is evidenced by the results of the t-test which shows a mean difference value of 5.968, which means that the average self-regulated learning of students is higher when using multimedia learning than not using it. The Sig (2-tailed) value of 0.012 indicates that Ha is accepted and Ho is rejected